Anti-Endothelial Cell Antibodies are not frequently elevated in hospitalized patients with COVID-19 - Henry, Brandon Michael; Benoit, Stefanie; Vikse, Jens; Favaloro, Emmanuel; Benoit, Justin; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
COVID-19 is now established to be associated with a thrombotic phenomenon, now called COVID-19 associated coagulopathy (CAC). Anti-Endothelial Cell Antibodies (AECA) are a heterogenous group of autoantibodies targeting various endothelial cell antigens or antigens adhering to endothelial cells, They are commonly observed in a variety of auto-immune and rheumatologic conditions, and were observed in patients with the severe acute respiratory syndrome (SARS) in 2005. We aimed to assess AECA status in patients with COVID-19 and their potential contributing role to endothelial injury and CAC. AECA identification was a relatively infrequent finding in COVID-19 patients on admission, and their presence, albeit in only 2/33 patients, was not associated with disease severity. However, as the autoantibodies were only measured at admission, we cannot exclude the possibility of pathogenic AECA developing later in the course of diseaseFurther studies using additional methods are needed to evaluate the presence and potential pathogenic role of AECA in later stages of COVID-19.